Theoretical Dynamics of Experimental Populations of Introduced and Native Blowflies (Diptera: Calliphoridae) - Dos Reis, S. F.; Teixeira, M. A.; Von Zuben, F. J.; Godoy, W. A C [UNESP]; Von Zuben, C. J. [UNESP] (My University, 1996)
Equilibrium dynamics in experimental populations of Chrysomya megacephala (F.) and C. putoria (Wiedemann), which have recently invaded the Americas, and the native species Cochliomyia macellaria (F.), were investigated using nonlinear difference equations. A theoretical analysis of the mathematical model using bifurcation theory established the combination of demographic parameters responsible for producing shifts in blowfly population dynamics from stable equilibria to bounded cycles and aperiodic behavior. Mathematical modeling shows that the populations of the 2 introduced Chrysomya species will form stable oscillations with numbers fluctuating 3-4 times in successive generations. However, in the native species C. macellaria, the dynamics is characterized by damping oscillations in population size, leading to a stable population level.
Keywords: Bifurcation theory; Chrysomya megacephala; Chrysomya putoria; Cochliomyia macellaria; Mathematical modeling; Population dynamics; animal; biological model; fly; mathematical computing; population dynamics; Animals; Diptera; Mathematical Computing; Models, Biological; Population Dynamics